2013
DOI: 10.2989/16085906.2013.815405
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to antiretroviral therapy adherence among patients with HIV in Bissau, Guinea-Bissau: A qualitative study

Abstract: Adherence is a decisive factor in achieving a successful response to antiretroviral therapy (ART) for HIV infection. No previous studies have been conducted regarding HIV treatment adherence in Guinea-Bissau. In this study we assessed barriers and facilitators to patient ART adherence. Semi-structured interviews were conducted with 20 adult, HIV infected individuals receiving ART at a HIV treatment centre in Bissau, Guinea-Bissau. The grounded theory method was used to gather and analyse data. Results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 40 publications
3
24
0
3
Order By: Relevance
“…In addition to non-adherence to ARV regimen, it has been previously argued that the use of non-prescription remedies may potentiate low retention in ART clinics (26). The authors identified among others, reasons for low retention in ART care to include the need to travel long distances to receive medication, and preference for faith and religious remedies over orthodox treatment (26, 27). In a descriptive cross-sectional study conducted in the Upper West Region of Ghana, patients’ suboptimal adherence to ART therapy was mainly attributed to shortage of drugs (42%) and side effects of ARVs (17%) (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to non-adherence to ARV regimen, it has been previously argued that the use of non-prescription remedies may potentiate low retention in ART clinics (26). The authors identified among others, reasons for low retention in ART care to include the need to travel long distances to receive medication, and preference for faith and religious remedies over orthodox treatment (26, 27). In a descriptive cross-sectional study conducted in the Upper West Region of Ghana, patients’ suboptimal adherence to ART therapy was mainly attributed to shortage of drugs (42%) and side effects of ARVs (17%) (4).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons attributed to low retention in ART care or clinics, for example, include financial cost, fear of stigmatization, the need to travel long distances to receive medication, food insecurity, lack of access to correct information, pill burden, and preference for faith and religious remedies compared to orthodox treatment (4, 26, 27). In a descriptive cross-sectional study conducted in the Upper West Region of Ghana, patients’ suboptimal adherence to ART therapy was mainly attributed to forgetfulness and shortage of drugs (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bahkan yang dirasakan adalah hal sebaliknya yaitu efek samping yang membuat informan utama tidak bertahan lama dalam menjalani terapi ARV. Hal ini sejalan dengan penelitian yang dilakukan oleh Rasmusen, et al (2013) bahwa aspek kemanfaatan terapi ARV yang dirasakan berdampak pada kepatuhan berobat pasien.…”
Section: "Belum Ada Manfaate Kae Sih Mual Karo Ora Doyan Mangan Habunclassified
“…This study showed that HIV-related knowledge was a determining factor for optimal adherence. 15 HIV-related knowledge may affect patient use, understanding, and utilization of health care information on HIV, hence limited health literacy is a known barrier to treatment adherence. 16 The aim of this cross-sectional study was to validate the findings of our previous study on barriers and facilitators to adherence and describe the association with HIV-related knowledge in Bissau, Guinea-Bissau.…”
Section: Introductionmentioning
confidence: 99%